Evidence for Nitrogen-bearing Species on Umbriel: Sourced from a Subsurface Ocean, Undifferentiated Crust, or Impactors? - Richard J. Cartwright; Riley A. DeColibus; Julie C. Castillo-Rogez; Chloe B. Beddingfield; William M. Grundy; Tom A. Nordheim (The Planetary Science Journal, 2023)
Near-infrared spectra of Umbriel and the other classical Uranian moons exhibit 2.2 μ m absorption bands that could result from ammonia (NH _3 ) bearing species, possibly exposed in the geologically recent past. However, Umbriel has an ancient surface with minimal evidence for recent endogenic activity, raising the possibility that more refractory species are present, and/or that NH _3 is retained over long timescales. We analyzed 33 spectra of Umbriel to investigate its 2.2 μ m band, along with three other absorption features we identified near 2.14, 2.22, and 2.24 μ m. We assessed the subobserver longitudinal distributions of these four bands, finding that they are present across Umbriel and may be spatially associated with geologic features such as craters and large basins. We compared the bands to 15 candidate constituents. We found that Umbriel’s 2.14 μ m and 2.22 μ m bands are most consistent with the spectral signature of organics, its 2.24 μ m band is best matched by NH _3 ice, and its 2.2 μ m band is consistent with the signatures of NH _3 –H _2 O mixtures, aluminum-bearing phyllosilicates, and sodium-bearing carbonates. However, some of these candidate constituents do not match Umbriel’s spectral properties in other wavelength regions, highlighting the gaps in our understanding of the Uranian moons’ surface compositions. Umbriel’s 2.14 μ m band may alternatively result from a 2 _ν _3 overtone mode of CO _2 ice. If present on Umbriel, these candidate constituents could have formed in contact with an internal ocean and were subsequently exposed during Umbriel’s early history. Alternatively, these constituents might have originated in an undifferentiated crust or were delivered by impactors.